2019
DOI: 10.6023/cjoc201903004
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Activity Screening of Novel Amide Derivatives Containing Aromatic Thioether Group

Abstract: A series of amide derivatives containing aromatic sulfide and sulfone groups synthesized in our previous work displayed excellent nematocidal activity at 200 μg/mL. In order to explore the effect of structural modification of the amide bridge on biological activity in a more delicate way, two series of novel target compounds were designed and synthesized by adopting amide group flipping and introducing N-sulfonyl substituted amide bonds. The bioassays indicated that the structural modification of the amide bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…2.2 Synthesis of the target compounds 2.2.1 General synthetic procedure for target compounds I-1-I-10 N-(2-((3-Chloro-5-(trifluoromethyl)pyridin-2-yl)thio)ethyl)-3-(difluoromethyl)-1-methyl-1H-pyrazole-4-carboxamide was synthesized according to the literature procedure. 24,25 A mixture of 3-chloro-5-(trifluoromethyl)pyridine-2-thiol (1.1 mmol), potassium carbonate (1.3 mmol) in dimethylformamide (DMF) (5 mL) was heated to 80°C and stirred for 10 min, followed by addition of N-(2-chloroethyl)-3-(difluoromethyl)-1-methyl-1H-pyrazole-4-carboxamide (1.0 mmol). Studies on the novel fungicidal pyridine sulfides www.soci.org…”
Section: Reagents and Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.2 Synthesis of the target compounds 2.2.1 General synthetic procedure for target compounds I-1-I-10 N-(2-((3-Chloro-5-(trifluoromethyl)pyridin-2-yl)thio)ethyl)-3-(difluoromethyl)-1-methyl-1H-pyrazole-4-carboxamide was synthesized according to the literature procedure. 24,25 A mixture of 3-chloro-5-(trifluoromethyl)pyridine-2-thiol (1.1 mmol), potassium carbonate (1.3 mmol) in dimethylformamide (DMF) (5 mL) was heated to 80°C and stirred for 10 min, followed by addition of N-(2-chloroethyl)-3-(difluoromethyl)-1-methyl-1H-pyrazole-4-carboxamide (1.0 mmol). Studies on the novel fungicidal pyridine sulfides www.soci.org…”
Section: Reagents and Instrumentsmentioning
confidence: 99%
“…24 Subsequently, the nematicidal and fungicidal activities were measured in turn to summarize the structure and activity relationships (SARs), in which compound h-IV was discovered to have a good nematicidal activity. 24 Surprisingly, the compound I-1 with excellent fungicidal activity was found through the preliminary biological activity screening (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%
“…and B. cinerea t at 50 μg/mL than those of Pyrimethanil. In addition, a series of novel thioether derivatives containing an amide group were prepared by Hua et al [56], and bioassays indicated that the target compounds had certain activities against G. zeae, R. solani, C. capsica, P. melongenae, B. cinerea, P. piricola, A. kikuchiana, and C. circumscissa. Among the tested compounds, compound 45 (Figure 9) displayed better fungicidal activity against C. capsici (81.7%) than that of Fluopyram.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…1). [15] In this project, combined with the fungicidal amide lead compound h-I-9 discovered in our previous work and fungicidal piperazine compounds P-1 and P-2 reported in literatures, [16][17][18][19][20][21] the amide derivatives containing 4-quinolone and piperazine substructures were designed, prepared and screened for their biological activity (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%